2016
DOI: 10.1007/s00221-016-4638-0
|View full text |Cite
|
Sign up to set email alerts
|

Perception of rotation, path, and heading in circular trajectories

Abstract: When in darkness, humans can perceive the direction and magnitude of rotations and of linear translations in the horizontal plane. The current paper addresses the integrated perception of combined translational and rotational motion, as it occurs when moving along a curved trajectory. We questioned whether the perceived motion through the environment follows the predictions of a self-motion perception model (e.g., Merfeld et al. in J Vestib Res 3:141–161, 1993; Newman in A multisensory observer model for human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…The activation of this representation through translations or rotations could lead to an altered sensitivity in self-motion perception. This is in accordance with a study by Nooij, Nesti, Bülthoff, and Pretto (2016), who found that the linear addition of translational and rotational components of the sensory input does not suffice to explain the perceived motion; instead, the components must be combined in a more complex manner. Interestingly, two other studies looking at the intravestibular interaction between otoliths and SCCs found that translation detection thresholds were increased with concurrent rotation (Crane, 2016;MacNeilage et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The activation of this representation through translations or rotations could lead to an altered sensitivity in self-motion perception. This is in accordance with a study by Nooij, Nesti, Bülthoff, and Pretto (2016), who found that the linear addition of translational and rotational components of the sensory input does not suffice to explain the perceived motion; instead, the components must be combined in a more complex manner. Interestingly, two other studies looking at the intravestibular interaction between otoliths and SCCs found that translation detection thresholds were increased with concurrent rotation (Crane, 2016;MacNeilage et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…There is psychophysical evidence that a vestibular signal indicating forward translation can influence the perception of curvilinear paths (Bertin & Berthoz, 2004). However psychophysical measurements of heading-discrimination ability from purely vestibular sources indicate a range of estimation thresholds from medium values in the region of 68-98 (MacNeilage, Banks, DeAngelis, & Angelaki, 2010;Telford et al, 1995) through to very high thresholds of 308 (Nooij et al, 2016). If vestibular heading were to be included as a constraint, it could not be a very narrow one based on human data.…”
Section: Model Designmentioning
confidence: 99%
“…For now, I will limit myself to studies that used random-dot flow stimuli and that provide data bearing directly on the inner workings of the new model. Except for a small set of studies mentioned earlier (Bertin et al, 2000;Bertin & Berthoz, 2004;Bertin & Israel, 2005;Ivanenko et al, 1997;Nooij et al, 2016;Telford et al, 1995), the majority of previous research on human heading perception in the presence of rotation has involved visual-vestibular conflict; the vestibular signal carries information that the observer is stationary and not undergoing rotation, while the visual information indicates both forward motion and a rotation component. However, the new curvilinear self-motion estimation model enables us to make predictions as to what should occur in these circumstances.…”
Section: Experiments 5 Model Evidence From Human Heading Psychophysicamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies begin to address this issue by focusing on interactions of translation and rotation signals arising from otolith and semicircular canals respectively, particularly in the horizontal plane. For example, researcher have designed experiments in which human subjects were instructed to navigate along a curved motion trajectory through passive driving or active walking (Ivanenko et al, 1997 ; Israël et al, 2005 ; Nooij et al, 2016 ). The subjects were then required to reproduce the experienced path by drawing, walking or driving a vehicle.…”
Section: Trajectory Of Self-motionmentioning
confidence: 99%